A cost effective cloud data centre capacity planning method based on modality cost analysis. (1st January 2013) - Bashroush, Rabih; Noureddine, Moustafa
In resource provisioning for data centres, an important issue is how resources may be allocated to an application to guarantee service level agreements (SLAs). Resource provisioning is usually guided by intuitive or heuristic expectation of performance. Such methodology, however, usually leads to more resources than necessary. A quantitative performance estimate may guide the provider in making informed allocations, so that acceptable SLAs may be provided in a cost-effective manner. In this work, we looked at breaking the application into isolated modalities (modality is a scenario in which an application is used) and measuring resource cost per modality. When breaking the application into modalities, resource cost is assessed in isolation. Results are then aggregated to estimate the overall resource provisioning requirements. A validation tool is used to simulate the load and validate the assumptions. This was applied to a commercially available solution and validated in a data centre setting.